DARI CARUT MARUT PENEGAKAN HUKUM DI LAUT MENUJU PENEGAKAN HUKUM YANG PROGRESIF - Anwar, Khaidir (Fakultas Hukum Universitas Lampung)
The study investigated the oferlap of authority in the managemen of the sea. research using normative judical approach. the result showd that need to be estabilished maritime law as